Tomographic reconstruction of the Earth’s magnetosheath from multiple spacecraft: a theoretical study - A. M. Jorgensen; TianRan Sun; Y. Huang; L. Li; R. Xu; L. Dai; Chi Wang (Earth and Planetary Physics, 2024)
Following our earlier work on tomographic reconstruction of the magnetosheath soft X-ray emissions with superposed epoch analysis of many images recorded from a single spacecraft we now explore the instantaneous reconstruction of the magnetosheath and magnetopause using a few images recorded simultaneously from a few spacecraft. This workis motivated by the prospect of possibly having two or three soft X-ray imagers in spacein the coming years, and that many phenomena which occur at the magnetopause boundary, such as reconnection events and pressure pulse responses, do not lend themselvesas well to superposed epoch analysis. If the reconstruction is successful — which we demonstrate in this paper that it can be — this collection of imagers can be used to reconstructthe magnetosheath and magnetopause from a single image from each spacecraft, allowing for high time resolution reconstructions. In this paper we explore the reconstruction using, two, three, and four spacecraft. We show that the location of the subsolar pointof the magnetopause can be determined with just two satellites, and that volume emissions of soft X-rays, and the shape of the boundary, can be reconstructed using three or more satellites.